Our “Emel” (“Aspiration”) (1930–1940) - Ismail Kerimov (Крымское историческое обозрение)
One of the most respected journals in the Crimean Tatar language, in 1930s was “Emel” (“Aspiration”), which was published in Pazarchik (Romania) from the 1st of January of 1930s up to the 1940s. “Emel“ was arabographic up to the end of the 1930s, and only the last issues were published in Latin. Totally there were published 154 issues. The style of the journal in logotype was shown like this: “Scientific, literary, public and economical journal. Published once in 15 days”. Chief editor of the journal was popular Crimean Tatar writer, publicist and public figure Mistergip Fazil (Ulkusal). Different problems of the language, literature, culture and public life were highlighted regularly and published in the journal. At the same time there were given critical articles, reviews on the results of the scientific conferences of 1927, 1929, 1934 and discussions of Crimean Tatar literary language materials. A very big amount of literary material was published and discussed there: fiction literature, poetry, drama. Lots of articles were devoted to Stalin` s policy in the USSR. Real reasons of repressions against kulaks (wealthy citizens of the USSR) were presented and analyzed, severe repressions against Crimean Tatar specialists: scholars, writers and teachers of the Crimea were highlighted on the pages of the journal. The given article also analyzes the content of the journal connected with the Crimean Tatar diaspora in Romania. The attribution of some pseudonyms and abbreviations are given as well.